Clinical diagnosis of idiopathic pleuroparenchymal fibroelastosis: A retrospective multicenter study. (December 2017) - Enomoto, Yasunori; Nakamura, Yutaro; Satake, Yasuomi; Sumikawa, Hiromitsu; Johkoh, Takeshi; Colby, Thomas V.; Yasui, Hideki; Hozumi, Hironao; Karayama, Masato; Suzuki, Yuzo; Furuhashi, Kazuki; Fujisawa, Tomoyuki; et al.
Abstract: Background: Although the accurate diagnosis of pleuroparenchymal fibroelastosis (PPFE) requires pathologic evaluation, this diagnosis is often suggested when the radiologic findings are consistent with typical PPFE and when pulmonary apical cap, which radiologically and pathologically mimics PPFE, can be excluded by confirming disease progression. The aim of this study was to evaluate the validity of the clinical diagnosis of idiopathic PPFE. Methods: We recruited 44 patients with idiopathic PPFE according to our modified diagnostic criteria: 1) a radiologic PPFE pattern (i.e., bilateral subpleural dense consolidation with or without pleural thickening in the upper lobes and less marked or absent involvement of the lower lobes), 2) radiologic confirmation of disease progression, and 3) exclusion of other lung diseases with identifiable etiologies. The patients' baseline characteristics and clinical course were reviewed. Results: The median age was 70 years, and 28 patients were males. The majority revealed emaciation, hypercapnia, and a high ratio of residual volume to total lung capacity. On chest computed tomography, 39 patients showed abnormal shadows in the lower lobes; more than half were classified as having usual interstitial pneumonia (UIP)/possible UIP pattern. Pneumothorax was the most frequent complication (33/44). The median overall survival time after diagnosis was 35.3 months. The presence of lower lobe UIP/possible UIP pattern did not show a significant prognostic impact. Conclusions: Using our diagnostic criteria, we could recruit relatively many patients with similar characteristics to those of idiopathic PPFE patients in the literature. The possibility of clinical diagnosis of idiopathic PPFE should be further discussed. Highlights: We propose criteria to clinically diagnose pleuroparenchymal fibroelastosis (PPFE). According to them, 44 patients were recruited regardless of the pathologic evidence. Their clinical findings were similar to those of idiopathic PPFE in the literature. Idiopathic PPFE can be diagnosed even without pathologic evaluation.